(INDIGENOUS WOMEN AND ECOLOGICAL JUSTICE: THE PEREMPUAN AMAN MOVEMENT IN ADVOCATING FOR THE INDIGENOUS PEOPLES BILL) : PEREMPUAN ADAT DAN KEADILAN EKOLOGIS: GERAKAN PEREMPUAN AMAN DALAM ADVOKASI RUU MASYARAKAT ADAT - Akbar, Taufik; Permata Sari, Qurnia Indah (CV Kalimasada Group, 2025)
This article examines the strategic role of indigenous women in advancing ecological justice through the PEREMPUAN AMAN movement, particularly in the advocacy for the Indigenous Peoples Bill. Using a qualitative descriptive approach, the study explores how indigenous women experience multiple layers of discrimination, including the loss of land rights, traditional knowledge, inheritance, and exclusion from political participation and development processes. The study highlights how PEREMPUAN AMAN mobilizes resources, builds cross-community solidarity, and frames ecological and gender justice issues as a social movement strategy. Findings reveal that indigenous women are not merely victims of exploitative policies and development but are also key actors in pushing for more inclusive policy transformations. This movement underscores the need to integrate ecological justice and indigenous women’s rights into public policymaking.